Issuer’s Liability for Misleading Information: Study of Article 80 Capital Market Law from Legal Liability Perspectivele of Article - Mochammad Rizky Maulana Maulana; Sang Ayu Putu Rahayu; Mayzura Kamila Sukma (Law Research Review Quarterly, 2026)
The capital market heavily relies on the principle of full disclosure to maintain investor trust and market efficiency. However, violations such as presenting misleading information in the prospectus remain a significant issue. The main problem addressed in this paper is the difficulty investors face in obtaining civil compensation when issuers provide inaccurate material facts, as regulatory enforcement tends to prioritize administrative sanctions over civil restitution. This study aims to analyze the issuer's liability for misleading information and examine the implementation of Article 80 of Law Number 8 of 1995 concerning the Capital Market from a legal liability perspective. This study employs a normative legal research method utilizing statutory and conceptual approaches. The findings reveal that while Article 80 establishes a robust foundation for civil liability based on fault, its practical execution is hindered by the heavy burden on investors to prove a direct causal link between the misleading information and their financial loss. Consequently, dispute settlements rarely result in actual compensation for public shareholders. In conclusion, the current disclosure settlement mechanism is inadequate to provide fair legal protection. It requires regulatory reinforcement to operationalize civil liability effectively, ensuring issuers are held accountable for financial restitutions to restore legal certainty in the Indonesian capital market.